Faktor Yang Berhubungan Dengan Unsafe Action Pada Pekerja Energy Equity Epic Sengkang Kabupaten Wajo - M.Gymnastiar; Nurmiati Muchlis; Yuliati (Window of Public Health Journal, 2026)
Unsafe acts are behaviors of individuals in the workplace that have the potential to cause accidents, both to themselves and others. This type of behavior significantly increases the likelihood of dangerous incidents that can result in serious injury and even death. This study aims to analyze the factors that influence unsafe behavior in workers. The method used is a quantitative, cross-sectional design. The sample was taken by saturation, involving the entire population of 42 workers. Data analysis was performed using the Chi-square test. The results showed that the variables of OHS training, supervision, knowledge, and tenure had no significant effect on unsafe acts (p> 0.05). In contrast, job fatigue significantly affects unsafe behavior (p ≤ 0.05). Based on these results, companies are expected to develop clear job descriptions aligned with worker competencies and conduct workload analyses to prevent fatigue and reduce the risk of unsafe acts.